Green Marketing: A Study of the Factors Influencing the Repurchase Decision for Javanony Herbal Products - Widyastuti, Sri; Santoso, Budi (UI Scholars Hub, 2021)
The green consumer movement is a reflection of people’s concern about the environment and has given rise to the green market. Companies that want to survive in this market must be able to apply a green label to all aspects of their business. This research aims to understand the influence of attitude, perceived value, and perceived price among customers on the decision to repurchase Javanony herbal products. The sampling technique in this study is purposive sampling. This study concludes that the attitude of customers who already have an understanding of green products is not completely supported by the company in applying green marketing to create higher value for its customers. Consumers are ready to pay for the extra value, will pay a premium price, and will repurchase only if they perceive extra value in the green product.